2014
DOI: 10.1177/0960327114522278
|View full text |Cite
|
Sign up to set email alerts
|

The effects of x-ray radiation on the eye development of zebrafish

Abstract: The toxic effects of x-ray radiation on eye development was measured using zebrafish as a model organism. Zebrafish embryos at 8 h post-fertilization (hpf) were irradiated using X-rays at doses of 1, 2, 4, and 8 Gy. At 24 and 48 hpf, x-ray radiation induced a significant increase in reactive oxygen species (ROS) content and cell apoptotic signals. Both of these increases were dose dependent and there were significant positive relationships between them at 24 hpf. At 48 and 72 hpf, the increase of ROS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Ionizing radiation is widely used in medical diagnostics, cancer-related therapy, and has additional industrial applications [ 7 ]. Known hazards associated with human exposure to ionizing radiation include: induction of cellular death, genetic mutations, and carcinogenesis [ 7 ]. In addition to direct cellular effects, radiation exposure can also damage cells through the generation of reactive oxygen species (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ionizing radiation is widely used in medical diagnostics, cancer-related therapy, and has additional industrial applications [ 7 ]. Known hazards associated with human exposure to ionizing radiation include: induction of cellular death, genetic mutations, and carcinogenesis [ 7 ]. In addition to direct cellular effects, radiation exposure can also damage cells through the generation of reactive oxygen species (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) are formed when ionizing radiation is absorbed by small molecules, primarily water, surrounding cellular bio-macromolecules. These ROS react with cellular contents, including DNA and proteins [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our measurements detected a notable reduction in body length, which suggests spinal cord curvature and growth delay. It is well known that different radiation qualities cause developmental deteriorations (41)(42)(43)(44), but only a few studies measured the degree of spinal curvature (19,20) and confirmed a linear dose dependent increase in severity on the fourth dpi at a dose level of 10 Gy or higher. Sayed and Mitani (45) showed spinal cord abnormality (body curvature) in the embryos of fish (Medaka) even after exposure to UV-A irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…In additional experiments, 24 hpf embryos were irradiated using sub-lethal X-rays at different doses 54 . Luciferase activity of untreated, 1.8 Gy and 2.7 Gy treated embryos was measured in vitro, 6 h after irradiation.…”
Section: Inhibition Of Luciferase Activity In Zebrafish Embryos Upon mentioning
confidence: 99%